Experimental investigation of nanoclay performance as an assistant in water based enhanced oil recovery method - Hamid Mohammad Soleimani; Mohammad Taghi Sadeghi (Scientific Reports)
Abstract The experimental analysis of nanoclay in enhanced oil recovery applications was rarely investigated. The main goal of this study is to analyze the flowing behavior of nanoclay as enhanced oil recovery fluid. After finding the most stable enhanced oil recovery fluid, the flow characteristic measurement was done. All of the experiments were performed in the ambient pressure and temperature where all of the core samples and thin sections are oil-wet in nature. Capabilities of nanoclay as an enhanced oil recovery fluid are determined in the static flow and flooding tests. The results of the Amott test (static) showed that the oil recovery from the core was 2.3 mL in the cetyl trimethyl ammonium bromide base fluid, 2.1 mL in the nano-fluid (nanoclay + cetyl trimethyl ammonium bromide), and 1.8 mL in the nanoclay. In the dynamic test, by examining the flooding test in the two modes of nano-fluid (approximately 3.5 h) and nanoclay (approximately 2.5 h) and recording the production curve over time, it was observed that the final production rate for the nano-fluid was approximately 79% and for the nanoclay, approximately 54.5% of the oil in-situ. Using nanoclay as an enhanced oil recovery fluid that is economical and environmentally friendly is the main finding of this study. Finally, it is founded that the optimum enhanced oil recovery fluid during the experiments is 0.5 wt% cetyl trimethyl ammonium bromide and 0.1 wt% nanoclay that is called nano-fluid.